“Candidatus Ethanoperedens,” a Thermophilic Genus of Archaea Mediating the Anaerobic Oxidation of Ethane - Cedric Jasper Hahn (American Society for Microbiology, 2020)
ABSTRACT Cold seeps and hydrothermal vents deliver large amounts of methane and other gaseous alkanes into marine surface sediments. Consortia of archaea and partner bacteria thrive on the oxidation of these alkanes and its coupling to sulfate reduction. The inherently slow growth of the involved organisms and the lack of pure cultures have impeded the understanding of the molecular mechanisms of archaeal alkane degradation. Here, using hydrothermal sediments of the Guaymas Basin (Gulf of California) and ethane as the substrate, we cultured microbial consortia of a novel anaerobic ethane oxidizer, “Candidatus Ethanoperedens thermophilum” (GoM-Arc1 clade), and its partner bacterium “Candidatus Desulfofervidus auxilii,” previously known from methane-oxidizing consortia. The sulfate reduction activity of the culture doubled within one week, indicating a much faster growth than in any other alkane-oxidizing archaea described before. The dominance of a single archaeal phylotype in this culture allowed retrieval of a closed genome of “Ca. Ethanoperedens,” a sister genus of the recently reported ethane oxidizer “Candidatus Argoarchaeum.” The metagenome-assembled genome of “Ca. Ethanoperedens” encoded a complete methanogenesis pathway including a methyl-coenzyme M reductase (MCR) that is highly divergent from those of methanogens and methanotrophs. Combined substrate and metabolite analysis showed ethane as the sole growth substrate and production of ethyl-coenzyme M as the activation product. Stable isotope probing demonstrated that the enzymatic mechanism of ethane oxidation in “Ca. Ethanoperedens” is fully reversible; thus, its enzymatic machinery has potential for the biotechnological development of microbial ethane production from carbon dioxide. IMPORTANCE In the seabed, gaseous alkanes are oxidized by syntrophic microbial consortia that thereby reduce fluxes of these compounds into the water column. Because of the immense quantities of seabed alkane fluxes, these consortia are key catalysts of the global carbon cycle. Due to their obligate syntrophic lifestyle, the physiology of alkane-degrading archaea remains poorly understood. We have now cultivated a thermophilic, relatively fast-growing ethane oxidizer in partnership with a sulfate-reducing bacterium known to aid in methane oxidation and have retrieved the first complete genome of a short-chain alkane-degrading archaeon. This will greatly enhance the understanding of nonmethane alkane activation by noncanonical methyl-coenzyme M reductase enzymes and provide insights into additional metabolic steps and the mechanisms underlying syntrophic partnerships. Ultimately, this knowledge could lead to the biotechnological development of alkanogenic microorganisms to support the carbon neutrality of industrial processes.